The Impact of Stock Market Performance on Foreign Portfolio Investment in China - Haider, Muhammad Afaq; Khan, Muhammad Asif; Saddique, Shamila; Hashmi, Shujahat Haider (International Journal of Economics and Financial Issues, 2017)
The research is aimed at investigating the impact of stock market performance and inflation on foreign portfolio investment (FPI) in China. For this purpose, time series quarterly data from 2007Q1 to 2015Q4 is used. On the basis of stationarity results, ARDL model is used to examine the impact of the stock market prices and inflation on FPI. The results show that there is significant positive impact of stock market performance on the FPI, whereas inflation is found to be negatively associated with the FPI. The study also reveals that some historical events like Asian financial crisis of 2008, and the Shanghai Composite Stock Index crash of 2015, significantly affected the foreign portfolio investment in China. The investors should consider these two factors while investing in foreign financial markets. Keywords: Stock Market Performance, Inflation, FPI, China JEL Classifications: F21, G11, O16, P45